Transfer Pricing and Developing Economies : A Handbook for Policy Makers and Practitioners - Cooper, Joel; Fox, Randall; Loeprick, Jan; Mohindra, Komal (Washington, DC: World Bank, 2016)
Recent years have seen unprecedented public scrutiny over the tax practices of Multinational Enterprise (MNE) groups. Tax policy and administration concerning international transactions, aggressive tax planning, and tax avoidance have become an issue of extensive national and international debate in developed and developing countries alike. Within this context, transfer pricing, historically a subject of limited specialist interest, has attained name recognition amongst a broader global audience that is concerned with equitable fiscal policy and sustainable development. Abusive transfer pricing practices are considered to pose major risk to the direct tax base of many countries and developing countries are particularly vulnerable because corporate tax tends to account for a larger share of their revenue.